Spartan Caregiver Support: Program Description and Key Findings During Michigan’s Stay-At-Home Order - White, Allison N.; Brodhead, Matthew T.; Sipila-Thomas, Emma S.; Miranda, David Ray G.; Long, Holly M.; Fisher, Marisa H. (Advances in neurodevelopmental disorders, 2023)
Objectives The purpose of this paper is to describe a university program, Spartan Caregiver Support, that provided free on-demand telehealth services to caregivers of people with autism during the State of Michigan’s 2020 Stay-at-Home order. Method Participants ( n = 17) were caregivers of people with autism residing within the State of Michigan. Participants engaged with program members over video-conference technology, where participants received specific advice to support social and behavioral needs. Results We found that caregivers reported a variety of social and behavioral concerns, including concerns related to problem behavior, social/play skills, school/academics, and daily living. Conclusions This program description provides a framework for how to deliver on-demand telehealth support to caregivers of people with autism, especially during moments of crisis or emergency.